2019
DOI: 10.1371/journal.pone.0221811
|View full text |Cite
|
Sign up to set email alerts
|

Gene dysregulation in peripheral blood of moyamoya disease and comparison with other vascular disorders

Abstract: ObjectiveMoyamoya disease (MMD) is a chronic occlusive cerebrovascular disease with unknown etiology, sharing many similar clinical symptoms with other vascular disorders. This study aimed to investigate gene dysregulation in peripheral blood of MMD and compare it with other vascular disorders.MethodsTranscriptomic profiles of 12 MMD patients and 8 healthy controls were obtained using RNA sequencing. Differentially expressed genes (DEGs) were identified and several were validated by quantitative real-time PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 76 publications
3
17
0
Order By: Relevance
“…Although there are still controversial results and the exact role of EPCs has not yet been conclusively clarified, many studies have demonstrated an intimate correlation between EPCs and the development of MA ( Table 4 ) [ 21 , 23 , 24 ]. Very recently, transcriptomic and metabolomic profiling approaches have been reported for discovering potential disease biomarkers in peripheral blood of MA patients [ 43 , 44 ]. Hur et al have first in vitro characterized early and late EPCs from a single MA patient, which shared some endothelial phenotypes but showed different morphology, proliferation rate, survival features, and gene expression profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are still controversial results and the exact role of EPCs has not yet been conclusively clarified, many studies have demonstrated an intimate correlation between EPCs and the development of MA ( Table 4 ) [ 21 , 23 , 24 ]. Very recently, transcriptomic and metabolomic profiling approaches have been reported for discovering potential disease biomarkers in peripheral blood of MA patients [ 43 , 44 ]. Hur et al have first in vitro characterized early and late EPCs from a single MA patient, which shared some endothelial phenotypes but showed different morphology, proliferation rate, survival features, and gene expression profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no solid evidence showing the direct pathological relationship between the GZMB under expression and the occurrence of CAD and RA, we have identified some diseases linked to GZMB and correlated with CAD and RA. For example, CAD was found to be correlated with Moyamoya Disease (MDD) (Peng et al, 2019), and pneumonia (Garcia-Laorden et al, 2016). Furthermore, Xing Peng et al discovered that MDD patients with downregulated GZMB were also enriched with the downregulated genes of CAD (Peng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, CAD was found to be correlated with Moyamoya Disease (MDD) (Peng et al, 2019), and pneumonia (Garcia-Laorden et al, 2016). Furthermore, Xing Peng et al discovered that MDD patients with downregulated GZMB were also enriched with the downregulated genes of CAD (Peng et al, 2019). Many other studies also supported a correlation between MDD and CAD (Livesay & Johnson, 2019; Nam et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 533 differentially expressed genes (DEGs) were identified for MMD. Up-regulated genes were mainly involved in ECM organization, whereas downregulated genes were primarily associated with inflammatory and immune responses [ 113 ]. Rare de novo copy number variation (CNV) screening was performed by Aloui et al in 13 MMD trios using whole exome sequencing (WES) read depth data and whole genome high density SNP array data.…”
Section: Genetic Association Studies and Sequencingmentioning
confidence: 99%